Identifying priority areas for tidal wetland restoration by integrating ecosystem services supply and demand mismatches - Lin, Shiwei; Li, Xiuzhen; Wu, Ruidong; Ma, Yuxi; Zhao, Wenzhen; Wang, Jiangjing (Frontiers in Marine Science, 2022)
Governments and non-governmental organizations have widely recognized tidal wetland restoration as a sustainable instrument to lessen the threat of climate change, which is reflected by the expansion of the spatial scale of coastal restoration projects. However, approaches to large-scale spatial planning of tidal wetland restoration remain sparse. Previous studies on site selection for restoration planning have focused on the potential supply of ecosystem services (ES) or restoration feasibility with less emphasis on the mitigation of the status of regional ES supply and demand mismatches. We developed a five-step workflow based on systematic conservation planning to identify priority areas for tidal wetland restoration and applied it to the coastal reclaimed areas of Shanghai, China. With this workflow, we analyzed the changes in spatial distribution and the potential ecosystem services supply and restoration costs of priority areas between the two different scenarios of ES demand ignored and ES demand considered. Results showed that the potential restorable areas only accounted for 31.4% (425.2 km²) of the original reclaimed area because of other land use demands (e.g., permanent basic farmland conservation). We extracted 50% of the potential restorable areas as priority areas based on Aichi Target 15. Compared with the ES demand-ignored scenario, the ES demand scenario resulted in a substantial increase in the priority areas of Baoshan District (~177%) and Pudong New Area (~15%) and a small decrease in Chongming District (~4%). No significant change in the potential ES supply for all priority areas was observed between the two scenarios. However, the total restoration cost of the ES demand scenario is 10% higher than that of the ES demand-ignored scenario. Our study highlights the importance of considering the status of regional ES supply and demand (mis)matches in large-scale spatial planning for tidal wetland restoration.